General model for analyzing data on the rate of reactive dissolution of poly-disperse particulate solids - Bhattacharya, Arijit (Chemical Engineering Journal, 2008)
A model has been presented which successfully simulates the experimentally observed integral batch reactive dissolution rate data while accounting for the poly-dispersity of the solid particulate charge. This allowed avoiding arbitrary assumptions about the particulate inventory and size independence of the mass transfer coefficient. There is also no need for a priori identification of the controlling regime, which can change from kinetic to mass transfer during the process, apart from the possibility of the shift with the specified process and operating conditions. The model was applied with equal ease to a simple isothermal reaction, an exothermic reaction with runaway potential and to a phase-transfer catalysis reaction with a complex mechanism. The model was shown to predict the time required for a specified extent of conversion of the particulate reactant or the rate of consumption of a key liquid reactant under a variety of process and operating conditions, like temperature, liquid reactant and the catalyst concentration, particle size, poly-dispersity of the charge and agitation speed. Such information is useful in reactor design and scale-up. Where dissolution is accompanied with a runaway reaction, the model can predict quantities of interest in hazard assessment and should aid safe reactor design. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: kinetic model; particle size distribution; poly-disperse solid reactant; reactive dissolution; reactive thermal hazard; solid-liquid PTC reaction

Kinetic modeling of liquid phase autoxidation of cumene - Bhattacharya, Arijit (Chemical Engineering Journal, 2008)
A new kinetic model for the liquid phase autoxidation of cumene has been developed utilizing the existing knowledge about the traditional free-radical mechanism involving the initiation of the free-radicals, the chain propagation and transfer and the various modes of radical termination. Unlike previous work, in the re-organized reaction network an important cross-termination step replaces an often used but less likely one and a new derivation of the rate model has been provided. A base set of rate parameters for the elementary steps within this reaction network were chosen, many of them were same or very similar to those published in the literature, with a few critical ones re-estimated for correct match with directly observed kinetic data reported in the literature on cumene oxidation in bench scale reactors. Embedding this kinetic sub-model within a simple reaction engineering model for a single air-sparged continuous cumene oxidator, the liquid oxidate composition at the reactor exit could be predicted that compared closely with some limited published data from an industrial reactor. It is hoped that the kinetic model presented here would be a useful tool in the analysis and design of other autoxidation reactors as well with minor adaptations. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: air-sparged continuous oxidator; cumene oxidation; free-radical mechanism; kinetic model; liquid phase autoxidation

Enhanced dual-effect of adsorption and photodegradation of SiO2 embedded TiO2 hybrid catalyst for improved decolourization of methylene blue - Sonar, Shilpa K.; Wagh, Reshma V.; Niphadkar, Prashant S.; Joshi, Praphulla N.; Deshpande, Shilpa S.; Awate, Shobhana V. (Water Air and Soil Pollution, 2013)
Dual-effects of adsorption and photodegradation over titania, silica embedded titania, silica and commercial Degussa P-25 samples were studied for the decolourization of methylene blue in aqueous medium. Silica embedded titania and silica were prepared using inexpensive polymeric version of ethyl silicate as a source of silica. Catalysts were characterized by X-ray diffraction, scanning electron microscopy, UV-Vis spectroscopy and low temperature (77 K) nitrogen adsorption measurements. Among all the catalysts, silica embedded titania has exhibited faster decolourization of methylene blue solution on account of the enhancement of adsorption followed by degradation. An amount of the catalyst and the initial dye concentration of MB solution were found to influence the decolourization activity. Compared to titania catalyst, silica embedded titania and Degussa P-25 have shown the red shift in their UV-Vis spectrum. The experimental data of the reaction fitted well to the pseudo first order kinetic model. In present studies, the adsorption mechanism for the decolourization of MB solution was found to be applicable for an intra particle diffusion model.
Keywords: Adsorption; kinetic model; Methylene blue; Photodegradation; Silica embedded titania

Pseudo-homogeneous kinetic model for esterification of acetic acid with propanol isomers over dodecatungstophosphoric acid supported on montmorillonite k10 - Gurav, Hanumant R.; Nandiwale, Kakasaheb Y.; Bokade, Vijay V. (Journal of Physical Organic Chemistry, 2014)
Esterification of acetic acid with propanol isomers such as isopropanol and naEuropropanol was carried out over dodecatungstophosphoric acid (DTPA), dodecamolybdophosphoric acid ammonium salt hydrate, and sodium tungstate hydrated purified supported on montmorillonite K10, which were characterized by powder XaEuroray diffraction, BrunaueraEuro'EmmettaEuro'Teller, and temperature programmed ammonia desorption. A pseudoaEurohomogeneous (PaEuroH) kinetic model was established for esterification of acetic acid with propanol isomers over DTPA supported on montmorillonite K10. Effects of various parameters such as reaction time, speed of agitation, particle size, temperature, percent catalyst loading, molar ratio and mixture of propanol isomer were investigated in detail. The 20% (w/w) DTPA/K10 was found to be an optimum solid catalyst with 82% naEuropropanol and 53% isopropanol conversion with 100% selectivity toward propyl acetate. The 20% (w/w) DTPA/K10 catalyst was found to be reusable for three cycles. The reaction follows secondaEuroorder kinetics with activation energies of 25.53aEuro?kJaEuro?mol(a?'1) and 28.15aEuro?kJaEuro?mol(a?'1) for isopropanol and naEuropropanol, respectively. PseudoaEurohomogeneous kinetic model fitted with R-2 value of trend line 0.999. This implies that esterification reaction is kinetically controlled owing to high activation energy. Copyright a (c) 2013 John Wiley & Sons, Ltd.
Keywords: Acetic acid; dodecatungstophosphoric acid; Esterification; kinetic model; montmorillonite K10

Environmentally benign catalytic process for esterification of renewable levulinic acid to various alkyl levulinates biodiesel - Nandiwale, Kakasaheb Y.; Bokade, Vijay V. (Environmental Progress & Sustainable Energy, 2015)
This study explores, the use of modified zeolite (Micro/Meso-HZ-5) obtained by desilication post-treatment as heterogeneous catalyst for esterification of biomass derived renewable levulinic acid (LA) with different alkyl alcohols such as methanol, ethanol, n-butanol, and n-octanol aiming to produce corresponding alkyl levulinate. This method of production of alkyl levulinates would be sustainable process, as it can be used as novel miscible diesel biofuels preventing global warming by decreasing atmospheric CO2. The LA conversion obtained over Micro/Meso-HZ-5 was higher than H-ZSM-5, which is due to the combined effect of increase in Bronsted acid sites, total acidity, and other properties such as BET surface area and the generation of mesoporosity. The maximum LA conversion of 91, 95, 96, and 98% with 100% selectivity toward alkyl levulinate was obtained, when LA was being esterified over Micro/Meso-HZ-5 with methanol, ethanol, n-butanol, and n-octanol, respectively, at optimal process parameters. Micro/Meso-HZ-5 catalyst was found to be reusable for six cycles. Furthermore, pseudo homogeneous (P-H) kinetic model of the esterification of LA with the studied four alcohols were established with R-2>0.99, using the experimental data. A P-H kinetic model implies that, the esterification reaction follows second order reversible kinetics. (c) 2014 American Institute of Chemical Engineers Environ Prog, 34: 795-801, 2015
Keywords: biofuels; Esterification; kinetic model; levulinic acid; meso-HZ-5; micro

Esterification of renewable levulinic acid to n-butyl levulinate over modified H-ZSM-5 - Nandiwale, Kakasaheb Y.; Bokade, Vijay V. (Chemical Engineering & Technology, 2015)
The synthesis of n-butyl levulinate, one of the most important biodiesel additives, by catalytic esterification of biomass-derived levulinic acid (LA) with n-butanol over modified H-ZSM-5 (micro/meso-HZ-5) in a closed-batch system is reported for the first time. The optimization of the reaction conditions such as the reactant molar ratio, the catalyst loading, the reaction time and the temperature was performed in view to maximize the yield of n-butyl levulinate. Micro/meso-HZ-5 was found to be the most efficient catalyst, with 98% yield of n-butyl levulinate and a reusability for six cycles, which is higher than reported in the literature. A possible catalytic mechanism for the esterification reaction is also proposed. A second-order pseudo-homogeneous model with R-2 > 0.97 confirmed that the esterification reaction is performed in the kinetic regime due to the high activation energy of 23.84 kJ mol(-1).
Keywords: Esterification; kinetic model; levulinic acid; Micro/meso-HZ-5; n-Butyl levulinate

Inhibition effect of N,N-diglycidyl-4-glycidyloxy aniline on photosensitized cationic polymerization of formulations involving resorcinol diglycidyl ether and poly(propylene glycol)diglycidyl ether - Harikrishna, Reghunathan (Journal of Photochemistry and Photobiology A-Chemistry, 2015)
Cationic photopolymerization studies of poly(propylene glycol)diglycidyl ether with and without 25 wt% of resorcinol diglycidyl ether were carried out in presence of bis(4-methylphenyl)iodonium hexafluorophosphate as photoinitiator. Analyses were carried out using polychromatic radiation at different temperatures in a photo differential scanning calorimeter. The formulations showed an enhancement in the rate of polymerization on addition of resorcinol diglycidyl ether. The same formulations when subjected to photosensitized polymerization in presence of 1-chloro-4-propoxy-9H-thioxanthen-9-one, showed a reverse behavior in rate due to partial absorption of radiation by resorcinol diglycidyl ether. Studies carried out on by the addition of N,N-diglycidy1-4-glycidyloxy aniline as inhibitor on the photosensitized formulations showed higher scavenging activity by inhibitor. The addition of nitrogen containing epoxy monomer as inhibitor can lead to its possible crosslinking within the matrix on polymerization along with a decrease in rate of polymerization without compromising on the final observed conversion. This effect can occur readily for non vitrifying systems. Thus, this observation provides an insight into its possible usage in a rate controlled photopolymerizable epoxy formulations. The photopolymerization kinetics were found to depend on the nature of generation, propagation and scavenging of active centers which are heavily dependent on diffusional restrictions imparted by in situ viscosity of the system. The kinetic estimations as well as evaluation of autocatalytic kinetic model are investigated. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Glycidyl ether; Inhibition; kinetic model; kinetics; Photopolymerization; Photosensitization